The Brighton book: [collection] (Brighton, Myriad Edition, 2005)
Welcome to Brighton, the city of delirious invention where no one has an excuse for leading a normal life. This popular seaside resort with its infamously seedy underbelly boasts one and a half piers, a royal palace and ridiculous house prices. Bawdy and beautiful like the place itself, these stories and pictures are peopled by some seeking the good life and others who, in one way or another, have reached the end of the line. This dazzling collection includes new fiction by Jeanette Winterson, Louis de BerniГЁres, Meg Rosoff and Ali Smith, and original words and pictures from Roy Greenslade (the commuter's lot), world-renowned Ukrainian photographer Boris Mikhailov (postcards from the seafront), Nigella Lawson (how to cook fish and chips), Diana Souhami (seduction at sea), Patti Smith's guitarist Lenny Kaye (Brighton Beach, NY), Piers Gough and John Riddy (the architecture of perpetual pleasure), cartoonist Woodrow Phoenix (at the end of the line), Miranda Sawyer on Brighton's offbeat, plus Posy Simmonds' sketchbook, Bonnie Greer on what it is to be English, Marjane Satrapi's graphic prayers for the livingand poems from Lee Harwood.